Analysis of AFPM machines with cylindrically shaped magnets using quasi-3D method. Issue 4 (3rd July 2017) - Rostami, Naghi; Rostami, Majid
Abstract : Purpose: The purpose of this paper is the fast and accurate modelling of surface-mounted Axial-Flux Permanent-Magnet (AFPM) machines equipped with cylindrical magnets using quasi-3D approach. Furthermore, the accuracy of the method is improved by using leakage coefficient, saturation coefficient and an appropriate permeance function. Design/methodology/approach: Quasi-3D approach is used for fast and accurate modelling of AFPM machines. Air-gap flux density distribution, induced back EMF, and produced cogging torque are calculated using the proposed method with reasonable accuracy. Findings: The results obtained by quasi-3D approach compared to Finite-Element-Analyses (FEA) shows how accurate, fast and efficient this method is. It is proved that, this method can be successfully applied to evaluate the performance of the AFPM machines. Originality/value: Effectiveness and accuracy of quasi-3D approach is assessed on different AFPM machines. Furthermore, to increase the accuracy of computations, the effects of the magnetic potential drop at iron parts of the machine are taken into account by using a saturation coefficient. Besides, the influence of the slot opening on the flux density distribution is taken into account by using an appropriate relative permeance function.